Gamisoyo-san ameliorates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease in mice by modulating the SIRT1–AMPK–NRF2 pathway - Ye-Lim Kim; Hyo-Jeong Jin; Jong Seong Roh; Seokyung Park; Yu-Ri Seo; Sang-Chan Kim; Kwang Il Park; Phil Hyun Song; Chang-Hyun Song (Molecular & Cellular Toxicology, 2026)

Synthesis and global warming potential prediction of novel hydrofluoroethers for high-resistivity engineering fluids - Byeongjun Park; Ye-Ri Kim; Jae Min Cho; Jong Hyeon Byeon; Seung Yul Kim; Tae Gyu Hwang; Sang Goo Lee (Journal of Environmental Chemical Engineering, 2026)

Molecular remodeling of the central auditory pathway in tinnitus revealed by RNA sequencing - Ha Hyun Song; Byeonghyeon Lee; Hyeon Joon Shin; Ye-Ri Kim; Subi Ham; Un-Kyung Kim; Incheol Seo; Da Jung Jung (Genes & Genomics, 2026)

NGS-based identification of a MYO7A mutation in a Korean family with DFNB2, a subtype of autosomal recessive non-syndromic hearing loss - Ye-Ri Kim; Byeonghyeon Lee; Hong-Joon Park; Tae-Jun Kwon; Un-Kyung Kim (Genes & Genomics, 2025)

Therapeutic effect of intraperitoneal dexamethasone on noise-induced permanent threshold shift in mice model - Byeonghyeon Lee; Min-Cheol Kim; Ye-Ri Kim; Jong-Heun Kim; Tae-Jun Kwon; Da Jung Jung; Un-Kyung Kim; Kyu-Yup Lee (Experimental Brain Research, 2024)

Identification of novel missense mutation related with non-syndromic sensorineural deafness, DFNA11 in korean family by NGS - Ye-Ri Kim; Hye-Min Kim; Byeonghyeon Lee; Jeong-In Baek; Kyu-Yup Lee; Hong-Joon Park; Un-Kyung Kim (Genes & Genomics, 2023)

Protective effect of berberine chloride against cisplatin-induced ototoxicity - Jong-Heun Kim; Jeong-In Baek; In-Kyu Lee; Un-Kyung Kim; Ye-Ri Kim; Kyu-Yup Lee (Genes & Genomics, 2022)
Background Cisplatin (CP) is an effective anticancer drug broadly used for various types of cancers, but it has shown ototoxicity that results from oxidative stress. Berberine has been reported for its anti-oxidative stress suggesting its therapeutic potential for many diseases such as colitis, diabetes, and vascular dementia. Objective Organ of Corti of postnatal day 3 mouse cochlear explants were used to compare hair cells after the treatment with cisplatin alone or with berberine chloride (BC) followed by CP. Methods We investigated the potential of the anti-oxidative effect of BC against the cisplatin-induced ototoxicity. We observed a reduced aberrant bundle of stereocilia in hair cells in CP with BC pre-treated group. Caspase-3 immunofluorescence and TUNEL assay supported the hypothesis that BC attenuates the apoptotic signals induced by CP. Reactive oxygen species level in the mitochondria were investigated by MitoSOX Red staining and the mitochondrial membrane potentials were compared by JC-1 assay. Results BC decreased ROS generation with preserved mitochondrial membrane potentials in mitochondria as well as reduced DNA fragmentation in hair cells. In summary, our data indicate that BC might act as antioxidant against CP by reducing the stress in mitochondria resulting in cell survival. Conclusion Our result suggests the therapeutic potential of BC for prevention of the detrimental effect of CP-induced ototoxicity.

Correction to: Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2019)

Exocyst Complex Member EXOC5 Is Required for Survival of Hair Cells and Spiral Ganglion Neurons and Maintenance of Hearing - Byeonghyeon Lee; Jeong-In Baek; Hyehyun Min; Seung-Hyun Bae; Kyeonghye Moon; Min-A Kim; Ye-Ri Kim; Ben Fogelgren; Joshua H. Lipschutz; Kyu-Yup Lee; Jinwoong Bok; Un-Kyung Kim (Molecular Neurobiology, 2018)

Application of a Collagen Patch Derived from Duck Feet in Acute Tympanic Membrane Perforation - Soo Hyeon Kim; Ju Yeon Jeong; Hyun Jung Park; Bo Mi Moon; Ye Ri Park; Ok Joo Lee; Md Tipu Sultan; Dong-Kyu Kim; Hae Sang Park; Jun Ho Lee; Chan Hum Park (Tissue Engineering and Regenerative Medicine, 2017)

Identification of a novel nonsynonymous mutation of EYA1 disrupting splice site in a Korean patient with BOR syndrome - Hui Ram Kim; Mee Hyun Song; Min-A Kim; Ye-Ri Kim; Kyu-Yup Lee; Jong Kyung Sonn; Jaetae Lee; Jae Young Choi; Un-Kyung Kim (Molecular Biology Reports, 2014)